Capabilities of Novel Carbon Nano Adsorbents in Evaluating the Extraction of 2-NP and HM from aqueous solutions - Asmaly, Hamza A.; Kabbashi, Nassereldeen Ahmed; Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Yassin, Mohamed A. (KBES, 2023)
This study primarily focused on evaluating the efficacy of Metal Oxide-infused Carbon Nano Adsorbents (CNAs), which included both Carbon Nanotubes and Carbon Nanofibers, in removing Cd+2, Cr+3, and 2-NP from water solutions. We synthesized and analyzed four distinct types of CNAs, each impregnated with either Al2O3, TiO2, Fe2O3, or Cu2O3. The metal content in these CNAs was determined by comparing their dry and calcined weights. To investigate their properties, we utilized various techniques such as Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area analysis, Energy-Dispersive Xray Spectroscopy (EDX), and Thermal Gravimetric Analysis (TGA). These methods helped us understand their morphological traits, surface areas, pore structures, metal oxide distributions, and thermal stabilities, thereby confirming their adsorption effectiveness for pollutants. The findings indicated that CNAs altered with metal oxides showed higher surface areas and adsorption abilities than their unmodified counterparts. Specifically, CNAs/TiO2 exhibited the most significant increase in surface area 140 m2/g and pore volume 0.460 cm3/g , which resulted in an enhanced adsorption capacity for Cd+3 at 11.4(mg/g), surpassing the 9.5(mg/g) capacity of pure CNAs with increased surface area of 100 m2/g , surpassing that of pure CNAs. This enhancement led to a significant improvement in adsorption capacities, elevating the uptake for Cr+3 from 32.2 to 52 (mg/g) and for 2-NP from 24.8 to 49.6(mg/g). This enhancement in adsorption efficiency is attributed to the increased surface area and improved surface chemistry due to the incorporation of Titania and Alumina, which proved more effective than modifications with copper oxide and Ferric oxide. These insights emphasize the significance of selecting appropriate metal oxides for modifying CNAs, as this can greatly impact their ability to target various contaminants, thus contributing to the development of more advanced water purification methods using CNAs/MO.